Docosahexaenoic acid supplementation in phenylketonuria: a systematic review - Alanís-Bernal, Manuel; Boada-Oller, Laia; Sojitra, Mihir (Frontiers in Nutrition, 2025)
BackgroundPhenylketonuria (PKU) is an inborn error of metabolism requiring a protein-restricted diet, which may predispose patients to deficiencies in long-chain polyunsaturated fatty acids (LC-PUFAs), particularly docosahexaenoic acid (DHA). Given the critical role of DHA in neurodevelopment and membrane function, supplementation has been proposed as a potential therapeutic adjunct in PKU. To systematically review clinical and biochemical outcomes associated with DHA supplementation in individuals with PKU.MethodsA systematic literature search was conducted in PubMed for studies published between January 1990 and July 2025. We included clinical trials, cohort studies, and observational studies assessing the effects of DHA or LC-PUFA supplementation in PKU. Data were extracted regarding study design, sample size, age, dosage, duration, and outcome measures. Risk of bias was assessed using the Cochrane tool and ROBINS-I as appropriate.ResultsA total of 18 studies met the inclusion criteria. DHA supplementation consistently increased erythrocyte and plasma DHA levels, and some trials reported improvements in visual evoked potentials, while cognitive outcomes remained inconsistent. No adverse effects were reported.ConclusionDHA supplementation appears to be a safe and effective strategy to correct LC-PUFA deficiency in PKU, with potential neurophysiological benefits. However, its impact on long-term neurocognitive development remains uncertain, and further high-quality studies are needed to clarify its clinical value.